Sosialisasi dalam pencegahan bullying di kalangan siswa SMP IT Sains Al-Qur’an Mekar Baru: Penelitian - Fadilaturrahmah, Fadilaturrahmah; Nasution, Atinarahmi; Lestari, Fadilla Ayu; Sari, Utami Dwika; Sari, Nurmaya; Harahap, Yulia Sari; Mutawaqilbilahtumanggor, Mutawaqilbilahtumanggor (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Bullying is a serious problem that frequently occurs in schools and can negatively impact students' psychological development and academic achievement. This study aims to describe efforts to promote and prevent bullying among junior high school (SMP) students. The method used was a qualitative descriptive approach through observation, interviews, and literature review related to anti-bullying programs in schools. The results showed that outreach activities through counseling, group discussions, and character development were effective in increasing students' understanding of the negative impacts of bullying. Furthermore, the role of teachers, school counselors, and parental support is crucial in creating a safe, inclusive, and bullying-free school environment. In conclusion, ongoing outreach and prevention strategies involving the entire school community are strategic steps to reduce the incidence of bullying among junior high school students.